Effect of Anadenathera macrocarpa (Benth) Brenan extracts in tomato, pepper and corn seedlings - Silva, Luciana Barboza; Lopes, Glauciany Soares; Carneiro, Eliane; de Souza, Sammy Nery; Filho, Manoel Lopes da Silva; Almeida, Fernandes Antonio (Científica, 2020)
The objective was to study the effect of ethanolic extracts of the leaves and bark of Anadenathera macrocarpa (angico-preto) on the germination and development of tomato, pepper and maize seedlings. For the bioassays, concentrations of 0, 250, 500 and 1,000 mg mL-1 were used. Fifty seeds of each plant species were used to evaluate daily germination and ten seedlings were used to evaluate growth. The primary root growth of the maize was stimulated by the 250 mg mL-1 concentration of the leaf extract and in the presence of the bark extract the growth was linear. The germination speed index and germination percentage increased when using the concentrations of 615.8 and 724.4 mg mL-1, respectively. The concentration of 654.9 mg mL-1 increased the hypocotyl length and that of 628.1 mg mL-1 increased the radicle length of pepper. The length of the tomato radicle was influenced by the concentrations; it was shorter as the concentration increased. Therefore, despite acting differently in each species, A. macrocarpa leaf and bark extracts interfere with the germination and growth of the tested crops.